The future of IsiZulu lies in Gauteng The importance of taking into account urban varieties for the promotion of African languages with special references to isiZulu - issues for a debate - (:unkn) unknown (My University, 2005)
Standard varieties of African languages in South Africa refer to norms dating back to the previous century, and do not take into account present-day urban varieties. The argument is that, due to the general cultural and political preeminence of the speakers of these varieties, whose attitudes will determine the development of African languages, they should be fully recognized, even if it means giving recognition to varieties that developped outside their traditionnal speaking areas.
Keywords: African Research